Spermiophagy in the spermatheca of Melipona bicolor lepeletier, 1836 (Hymenoptera, Apidae, Meliponini) - Cruz-Landim, C. da [UNESP] (My University, 2002)
The presence of spermatozoa in vesicles in the cytoplasm of the epithelial cells that constitute the spermathecal wall of Melipona bicolor queen (Meliponini) is discussed in relation to the organ structure. The epithelial wall is lined by an apparently continuous cuticle in the luminal surface that should be a non-transposable barrier to the luminal spermatozoa. However, some spermatozoa were seen crossing the cuticle through interruptions that was first interpreted as sectioning defects. Nevertheless, the sperm cells in well-structured cytoplasmic vesicles, bound by membranes and sometimes associated to multivesicular bodies, as well as cytoplasmic structures representative of intracellular digestion and the occurrence of the phenomenon in two of the three spermathecae studied, suggest a real spermiophagic hole in the spermathecal epithelial cells.
Keywords: Animal; Animal disease; Bee; Cytology; Electron microscopy; Female; Histology; Male; Physiology; Reproduction; Spermatozoon; Ultrastructure; Animals; Bees; Female; Male; Microscopy, Electron; Reproduction; Spermatozoa